Results of Surgical Ttreatment of Patients With Cerebral Aneurysms in the Acute Period of Hemorrhage Transported Over a Considerable Distance - E. A. Vorobyov; V. G. Dashyan; N. V. Savvina; M. Y. Makievskij; S. A. Chugunova; I. S. Yakhontov; F. V. Gerasimov; S. I. Efremov (Неотложная медицинская помощь)
Relevance. To provide emergency specialized neurosurgical care to patients living in rural areas, medical evacuation to a neurosurgical hospital is required. Despite the fact that medical evacuation is a necessary stage of medical care, there are not enough studies on the impact of transportation of patients with a ruptured cerebral aneurysm over long distances. There is little information about the time intervals for transportation, the timing of the start of treatment and the outcomes of the disease in patients who are at a considerable distance from the neurosurgical hospital.Aim of the study. To analyze the impact on the extensive results of surgical treatment of patients with cerebral aneurysm rupture.Material and methods. A retrospective analysis of the results of surgical treatment of 145 patients with cerebral aneurysm rupture in the acute period of hemorrhage, hospitalized in the regional vascular center of the State Budgetary Institution of the Sakha Republic (Yakutia) “Republican Hospital No. 2 — Center for Emergency Medical Aid” in the period from 01.01.2017 to 31.12.2018. Patients were divided into two groups: Group I — patients from remote areas of the Republic of Sakha (Yakutia) who underwent medical evacuation by the Disaster Medicine Service of the Sakha Republic (Yakutia); Group II — hospitalized from the territory of the city of Yakutsk and its nearest suburbs.Results. 145 patients were hospitalized at the regional vascular center in Yakutsk. Sanaviation (Sanitary Aviation) delivered 91 patients from the districts of the republic to the regional vascular center (62.8% of the total number of patients) (Group I), 54 patients (37.2%) were hospitalized from the territory of the urban district of Yakutsk (Group II). The distance of transportation by ambulance aircraft in Group I ranged from 45 to 1330 kilometers. Deterioration from admission to the local medical organization to admission to the regional vascular center was noted in 8 patients (8.8%), improvement in the condition in 25 (27.5%) patients, there were no dynamics of changes in the state of 58 (63.7%) patients. The total number of deaths in two groups of patients was 11 (12.1%) patients. Postoperative mortality had no statistically significant differences between the two study groups: in Group I — 7.7% (7 patients), in Group II — 7.4% (4 observations) (p=1,000).Conclusions. With an established system of medical evacuation, transportation over a considerable distance does not worsen the course of the disease and the results of surgical treatment of patients with cerebral aneurysm ruptures in the acute period of hemorrhage.